Role of outstretched forelegs of flying beetles revealed and demonstrated by remote leg stimulation in free flight - Li, Yao (2018)
In flight, many insects fold their forelegs tightly close to the body, which naturally decreases drag or air resistance. However, flying beetles stretch out their forelegs for some reason. Why do they adopt this posture in flight? Here, we show the role of the stretched forelegs in flight of the beetle Mecynorrhina torquata. Using leg motion tracking and electromyography in flight, we found that the forelegs were voluntarily swung clockwise in yaw to induce counter-clockwise rotation of the body for turning left, and vice versa. Furthermore, we demonstrated remote control of left–right turnings in flight by swinging the forelegs via a remote electrical stimulator for the leg muscles. The results and demonstration reveal that the beetle’s forelegs play a supplemental role in directional steering during flight.